(untitled) (Penerbit UTHM, 2026)
Smart Health and Sustainability explore how innovations in electronics, biomedical engineering, and IoT are addressing today’s healthcare and environmental challenges. Showcasing real-world projects from the Faculty of Electrical and Electronic Engineering, UTHM, this book highlights smart systems for health monitoring, environmental safety, and personal well-being. Aimed at inspiring students and researchers, it underscores how interdisciplinary engineering can drive intelligent, sustainable solutions for a better future.